2022
DOI: 10.1002/hbm.25998
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortex layer segmentation using diffusion magnetic resonance imaging in vivo with applications to laminar connections and working memory analysis

Abstract: Understanding the laminar brain structure is of great help in further developing our knowledge of the functions of the brain. However, since most layer segmentation methods are invasive, it is difficult to apply them to the human brain in vivo. To systematically explore the human brain's laminar structure noninvasively, the K-means clustering algorithm was used to automatically segment the left hemisphere into two layers, the superficial and deep layers, using a 7 Tesla (T) diffusion magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
1
0
0
Order By: Relevance
“…Also, the variation of FA in the cortical lamina is determined directly by the organizational structure of myelinated bers [39], and the cortical depth pro les of diffusivity re ect similar laminar structures correlated with cell density [40]. Moreover, our ndings are consistent with recent in-vivo studies [17,41], revealed that both myeloarchitectonic and cytoarchitectonic structures in uence diffusion properties in the cortex. We also found that diffusional anisotropy nonlinearly increased and diffusivity linearly decreased with layer increase in cortical regions, especially in prefrontal (IFC) and visual cortexes.…”
Section: Layer-dependent Microstructure Cortical Regionssupporting
confidence: 88%
“…Also, the variation of FA in the cortical lamina is determined directly by the organizational structure of myelinated bers [39], and the cortical depth pro les of diffusivity re ect similar laminar structures correlated with cell density [40]. Moreover, our ndings are consistent with recent in-vivo studies [17,41], revealed that both myeloarchitectonic and cytoarchitectonic structures in uence diffusion properties in the cortex. We also found that diffusional anisotropy nonlinearly increased and diffusivity linearly decreased with layer increase in cortical regions, especially in prefrontal (IFC) and visual cortexes.…”
Section: Layer-dependent Microstructure Cortical Regionssupporting
confidence: 88%
“…To summarize the existing literature, previous attempts using machine learning and deep learning techniques have shown the possibilities to segment the cortical layers (Bastiani et al, 2016;Zhang et al, 2022). Thus, we decided to take it one step further by using a more advanced network, such as nnU-Net (Isensee, Jaeger, et al, 2021), which has been developed and showed great segmentation results specifically targeting the medical image processing field.…”
Section: Related Workmentioning
confidence: 99%